Pengaruh Perbandingan Tepung Ubi Jalar Ungu Dan Tepung Kedelai Terhadap Karakteristik Flakes Sebagai Pangan Fungsional - Mei Rani, Ratna; Ekawati, I Gusti Ayu; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 2 (2021): Jurnal ITEPA, 2021)
The research aim to determine the effect of ratio purple sweet potato flour and soybean flour on characteristics functional flakes and determine the exact ratio of purple sweet potato flour and soybean flour which can produce functional flakes with the best characteristics. The Completed Randomized Design was used in this research consisting ratio of purple sweet potato flour and soybean flour including (P1) 90% : 10%, (P2) 80% : 20%, (P3) 70% : 30%, (P4) 60% : 40%, (P5) 50% : 50%. The data obtained were analyzed by variance and if the treatment had significant effect followed by Duncan Multiple Range Test (DMRT). The result showed that flakes with comparison of 70% purple sweet potato flour and 30% soybean flour is the best treatments with criteria moisture content of 3.05%, ash content of 2.09%, protein content of 17.04%, crude fiber 3.76%, anthocyanin total 21.07 mg/100g, antioxidant activity 39.55%, water absorption 165.66% and color is purple and like, aroma is like, texture is crispy and like, taste is like and overall acceptance is like.